-66-7x=-13x+18

Simple and best practice solution for -66-7x=-13x+18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -66-7x=-13x+18 equation:


Simplifying
-66 + -7x = -13x + 18

Reorder the terms:
-66 + -7x = 18 + -13x

Solving
-66 + -7x = 18 + -13x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '13x' to each side of the equation.
-66 + -7x + 13x = 18 + -13x + 13x

Combine like terms: -7x + 13x = 6x
-66 + 6x = 18 + -13x + 13x

Combine like terms: -13x + 13x = 0
-66 + 6x = 18 + 0
-66 + 6x = 18

Add '66' to each side of the equation.
-66 + 66 + 6x = 18 + 66

Combine like terms: -66 + 66 = 0
0 + 6x = 18 + 66
6x = 18 + 66

Combine like terms: 18 + 66 = 84
6x = 84

Divide each side by '6'.
x = 14

Simplifying
x = 14

See similar equations:

| (5x+3x)+(7x+3)= | | (a-5)(5a-1)= | | 2.798x+4=17.9 | | 10(-2x+1)=-19(r+1) | | -3x-16=2x+4 | | sqrtx+10=2 | | (4+1.3)*2.1= | | 15(4y+14)= | | 5x-(-2)=3 | | -2x+9x-4x=0 | | (1-4u+v)(-9)= | | 5(1)-y=3 | | 5x-(0)=3 | | 9-2(5-4)= | | 8d+7d= | | d+d+2+d+4+d+6= | | 32r=10 | | 32=10 | | 10=rt | | 2(3z-2)+8=38 | | 2(2x+4)=-3(5x-3) | | -4(x-8)-7=7(x-6) | | 6(x+2)-8=4x+2(1+x) | | 6x-8=4x+18 | | (9x+20)=28 | | 8-5(x+3)=x-29 | | 105=15+18v | | 3(x+5)-4=6x-3(-4+x) | | 10b+-2=7b-7.4 | | x=31.64165854+-1.536585366y | | (12a-3b-5c)-5(-5a+4b-6c)= | | -23.4/_1/3 |

Equations solver categories